Decoupling touch from sex: gender(ed) representations of physical intimacy in the cuddle industry - Santos, Paulo (Frontiers in Sociology, 2023)
The present study explores the resistance to and potential transformation of hegemonic gender norms regarding intimacy and sexuality through an instrumental case study of the so-called “professional cuddlers”, a category of body workers that have proliferated in Europe since 2015 offering paid sessions of non-sexual physical intimacy. Despite efforts to frame the service as a form of therapy, professional cuddling is often misunderstood as a front for prostitution, and practitioners must frequently deal with unwanted sexual advancements. Drawing from a 3-year online ethnographic study of cuddling services, the dataset includes 10 in-depth interviews informed by a previous qualitative analysis of 46 newspaper articles, 16 forum discussions, and 25 websites related to such practices. Findings demonstrate that the representational limbo experienced by practitioners could be better understood as a product of the “sexusociety”. Though it is unclear whether professional cuddling has any significant impact on hegemonic gender norms, results show that it nonetheless deconstructs the normative landscape through the enactment of alternative scripts.